Analyzing the Effects of Bank Digitalization on Bank Competition and Profitability in Central Asia: Insights from Kyrgyzstan and Kazakhstan - Emil BEGIMKULOV; Mónika KUTI (Eurasian Journal of Business and Economics)
This research investigates how bank digitalization influences competition and profitability within the banking industries of Kyrgyzstan and Kazakhstan over the period from 2012 to 2023. The bank digitalization index is estimated following the System Dynamics Approach. The assessment of banking competition is conducted using the Lerner Index and the Boone Indicator. The relationships between bank digitalization, competition, and profitability are analyzed through a two-step Generalized Method of Moments analysis. Findings reveal that in Kyrgyzstan, digital transformation enhances bank competition and efficiency, advocating local banks to accelerate digital adoption to leverage favorable market conditions. Conversely, in Kazakhstan, despite higher levels of digitalization, the impact on competition and profitability remains insignificant. This highlights the need for banks to persistently expand their digital capabilities beyond current innovations to stay competitive and improve financial results. The study recommends that policymakers foster an environment that nurtures innovation and sustains competitive equilibrium in the banking industry.